Globalization and Child Health in Developing Countries: The Role of Democracy - Anna Welander; Carl Hampus Lyttkens; Therese Nilsson (Lund University, School of Economics and Management, Department of Economics, 2014)
Good health is crucial for human and economic development. In particular poor health in childhood seems to be of utmost concern since it causes irreversible damage and have implications later in life. Recent research suggests globalization is a strong force affecting adult and child health outcomes. Yet, there is much unexplained variation with respect to the globalization effect on child health, in particular in low- and middle-income countries. One factor that could explain such variation across countries is the quality of democracy. Using panel data for 70 developing countries between 1970 and 2009 this paper disentangles the relationship between globalization, democracy, and child health. Specifically the paper examines how globalization and a country's democratic status and historical experience with democracy, respectively, affect infant mortality. In line with previous economic research, results suggest that globalization reduces infant mortality and that the level of democracy in a country generally improves child health outcomes. We also find that democracy matters for the size of the globalization effect on child health. If e.g. Côte d'Ivoire was a democracy in the 2000-2009 period, this effect would translate into 1,200 fewer infant deaths in an average year compared to the situation without democracy.
Keywords: F63; F68; I15; P16; 330; Globalization; Democracy; Child Health; Developing Countries